2021
DOI: 10.18617/liinc.v17i1.5593
|View full text |Cite
|
Sign up to set email alerts
|

Retractions and post-retraction citations in the COVID-19 infodemic: is Academia spreading misinformation?

Abstract: The speed in producing information and the rush to publish scientific articles on COVID-19 in several knowledge areas have resulted in what is known as an infodemic also in the scientific field, potentially producing inaccurate information and sources of misinformation at scholarly communication. This has led to some articles being retracted or withdrawn due to unintentional errors or deliberate misconduct, but they continue to be cited. This article (i) gives an overview of the COVID-19 retracted articles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
10
0
2
Order By: Relevance
“… Theis-Mahon and Bakker (2020) reported that 475 (69.34%) out of the 685 postretraction citations to retracted dentistry papers were positive. Santos-d’Amorim et al (2021) investigated 214 postretraction citations to one retracted Covid-19 paper and identified 64 (30%) positive, 81 (38%) negative, and 69 (32%) neutral citations. Studies that more deeply analyzed citation contexts (e.g., beyond the tone) focused only on a single retracted paper and its citations ( Fulton, Coates et al, 2015 ; Schneider et al, 2020 ; Suelzer et al, 2019 ; van der Vet & Nijveen, 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“… Theis-Mahon and Bakker (2020) reported that 475 (69.34%) out of the 685 postretraction citations to retracted dentistry papers were positive. Santos-d’Amorim et al (2021) investigated 214 postretraction citations to one retracted Covid-19 paper and identified 64 (30%) positive, 81 (38%) negative, and 69 (32%) neutral citations. Studies that more deeply analyzed citation contexts (e.g., beyond the tone) focused only on a single retracted paper and its citations ( Fulton, Coates et al, 2015 ; Schneider et al, 2020 ; Suelzer et al, 2019 ; van der Vet & Nijveen, 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The efforts to identify flaws in research are not new, but the concerns associated with the reliability of data and the reproducibility of COVID-19 studies have ignited debates on the subject (Bommier;Stoeklé;Hervé, 2021; EVIDENCE ON RETRACTIONS IN BRAZIL https://doi.org/10.1590/2318-0889202133e210001 Bramstedt, 2020;Santos-d' Amorim;Melo;Santos, 2021;Vlasschaert;Topf;Hiremath, 2020). Aiming to improve these mechanisms, the editors of The Lancet Group, after the negative repercussions involving a retraction in The Lancet (Mehra;Ruschitzka;Patel, 2020;The Lancet Editors, 2020a), have redefined their peer review process.…”
Section: International Collaborationmentioning
confidence: 99%
“…However, over the years and more recently, in the scenario of the Coronavirus Disease 2019 (COVID-19) pandemic, serial retractions, including cases in reputable journals such as The Lancet and the New England Journal of Medicine, have promoted debates on the issue (Bramstedt, 2020;Freckelton, 2020). Even after retraction and wide media dissemination (Piller, 2021), some articles continue to be cited, generating misinformation, setbacks and, within the scope of issues associated with the ongoing pandemic, public health problems that could impact the entire globe (Péretz et al, 2021;Santos-d' Amorim;Melo;Santos, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khalifa e Ahmed (2021), por exemplo, identificaram casos de artigos científicos que foram aceitos no primeiro dia de submissão. É nesse contexto que a noção de infodemia também é percebida na comunicação científica, cuja torrente de artigos, preprints, protocolos e relatórios de pesquisas conduzidos nesse senso de urgência dão margem tanto para a incidência de erros não intencionais como para a má conduta deliberada na pesquisa científica (Bramstedt, 2020;Jesus-Silva & Antonio, 2021;Santos-d'Amorim, Melo, & Santos, 2021;Whitmore et al, 2020).…”
Section: Introductionunclassified